2004
DOI: 10.1021/om034368r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and CO2 Reactivity of a Two-Coordinate (Carbene)copper(I) Methyl Complex

Abstract: Two-coordinate copper(I) acetate and copper(I) methyl complexes, bearing an N-heterocyclic carbene (NHC) supporting ligand, have been synthesized and structurally characterized, and the stability of the monodentate acetate has been examined by DFT calculations. The methyl complex readily inserts carbon dioxide at ambient temperature and pressure, regenerating the acetate in near-quantitative yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
141
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 179 publications
(159 citation statements)
references
References 29 publications
18
141
0
Order By: Relevance
“…The complexes (SIPr)-Cu(OAc) (1) and (IMes)Cu(OAc) (2) (SIPr ) 1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene; IMes ) 1,3-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene) can be prepared in reactions analogous to the synthesis of (IPr)Cu(OAc). 30 Complexes 1 and 2 have been characterized by 1 H and 13 C NMR spectroscopy and elemental analysis. In addition, single-crystal X-ray diffraction studies of 1 and 2 have confirmed their identity (Figures 1 and 2 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The complexes (SIPr)-Cu(OAc) (1) and (IMes)Cu(OAc) (2) (SIPr ) 1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene; IMes ) 1,3-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene) can be prepared in reactions analogous to the synthesis of (IPr)Cu(OAc). 30 Complexes 1 and 2 have been characterized by 1 H and 13 C NMR spectroscopy and elemental analysis. In addition, single-crystal X-ray diffraction studies of 1 and 2 have confirmed their identity (Figures 1 and 2 and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to (IPr)Cu(OAc), the acetate ligands of 1 and 2 both exhibit a κ 1 -coordination mode, and Sadighi et al have suggested the possibility that the preferred κ 1 -coordination mode (in preference to the κ 2 -coordination mode) is the result of an intermolecular interaction between the distal oxygen and a hydrogen of a second carbene ligand. 30 The distance between Cu and the distal oxygen is shorter for the IMes complex 2 (2.831 Å) than for the SIPr complex 1 (3.082 Å) but is similar to that of (IPr)Cu(OAc) {2.868(4) Å}. The similar bond distances of 2 and (IPr)Cu(OAc) suggest that electronic effects of the carbene ligand likely govern the interaction, a result supported by density functional calculations on (NHC)-Cu(acetate), which show conversion of the acetate ligand from κ 2 to κ 1 upon energy minimization, presumably driven by the stability of linear, two-coordinate geometries for d 10 -Cu(I).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations